PENGEMBANGAN MEDIA PEMBELAJARAN HARMONY DIGITAL MUATAN PENDIDIKAN PANCASILA MATERI PANCASILA UNTUK SISWA KELAS II SEKOLAH DASAR - Viana, Wiwit Elma; Yustiana, Sari (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2025)
Technology plays an important role in improving the quality and quality of education. To improve the quality of education, learning media is needed, especially Pancasila Education subjects. Creative and innovative learning media can help students understand the material. Digital learning media helps teachers in delivering interesting material and maximizing the spirit of student involvement in learning so that learning is not boring. But in reality, in the learning process of Pancasila education, the application of digital learning media is less considered, due to the limited use of technology among educators. This study aims to determine the feasibility and practicality of digital-based Harmony learning media content of Pancasila Education material for grade II elementary school students. The method used in this research is research and development (R&D) with the ADDIE model. This research involved two expert validators and 22 respondents in the SD Negeri Poncoruso Education unit. The data collection technique used expert validation questionnaires, teacher response questionnaires and student response questionnaires. Expert validation questionnaires are used to determine the feasibility of the media. Student and teacher response questionnaires were used to determine the practicality of the media. The findings of expert validation show an average percentage of 92% and these findings are included in the very feasible category. While the findings based on student responses showed an average percentage of 95.24% and teacher responses averaged a percentage of 94% with a very practical category.